(untitled) (Gaceta Técnica, 2019)
The objective of this article is to present an investigation in which the case study method was used using a group control, to apply the inverted class model in a rigid body mechanics course. The students of the group have received the course with the investment model, while the control group with the traditional method is based on lectures. This qualitative-quantitative study collected information from two sources: final course grades and student surveys. As a result, the final scores of group B were also higher than group A (p = 0.039). Group B ratings related to the percentage of pre-recorded conference reviews. In the surveys, group B positively rated the application of the model at 8,3 ± 1,4. In conclusion, that the inverted class promotes student self-learning, which is recommended in the contents related to Physics and Mathematics